Optimizing Raw Material Inventory Using the EOQ Method (Business Case “Madumongso Bu Binti” - Wahyuningsih, Diah Ayu; Fauji, Diah Ayu Septi (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This research aims to analyze the most economical number of orders for sticky rice raw materials to fulfill supplies at the "Madumongso Bu Binti" business and determine safety stock and reorder points.Design/Methode/Approach : This type of reseacrh is descriptive with a quantitative approach and the method used is EOQ (Economic Order Quantity). The subject of this research is “Madumongso Bu Binti” Business, and the object is the supply of sticky rice raw materials. The data collection technique was carried out using interviews, observation, and documentation.Research Finding : The research results show that the optimal purchase of sticky rice raw materials is 786 kilograms per order with a purchase frequency of 8 times a year or once every 1.5 months. The safety stock required by the company is 127 kilograms and the Re-Order Point for sticky rice raw materials that must be reordered before stock runs out is 159 kilograms. Keywords : inventory, EOQ, and sticky rice raw material